Glengarry Glen Ross - Foley, James; Al Pacino, 1940-; Ed Harris; Jack Lemmon (USA GGR, 1992)
Times are tough in a New York office; the salesmen (Shelley Levene, Ricky Roma, Dave Moss, and George Aaronow) are given a strong incentive by Blake to succeed in a sales contest. The prizes? First prize is a Cadillac Eldorado, second prize is a set of steak knives, third prize is the sack! There is no room for losers in this dramatically masculine world; only ""closers"" will get the good sales leads. There is a lot of pressure to succeed, so a robbery is committed which has unforseen consequences for all the characters.
An examination of the machinations behind the scenes at a real estate office.
David Mamet
Language : English Subtitle : English
Keywords: Drama